2015
DOI: 10.13187/er.2015.97.560
|View full text |Cite
|
Sign up to set email alerts
|

Risky Driving Attitudes in Ghana: Is the Use of Fear-Based Messages Operational?

Abstract: Scare tactics are often used in road safety campaigns even though years of research into fear appeals have yielded inconsistent results. In Ghana, where all efforts are being made to reduce traffic accidents, the use of fear appeals and threat of enforcement has not been spared. In an experimental study, the researchers investigated the effectiveness of this message on risky driving attitude and also explored the effect of an alternative strategy, fear of prosecution. Findings from this study suggest that fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The articles on education clearly demonstrate that knowledge about road safety and traffic signs and fear-based appeals do not translate into a commensurate attitudinal and behavioural change on the road (Anakwah et al, 2015;Blantari et al, 2005;Johnson & Adebayo, 2011). Our findings on the use of the media, especially threat-based messages, align with other reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles on education clearly demonstrate that knowledge about road safety and traffic signs and fear-based appeals do not translate into a commensurate attitudinal and behavioural change on the road (Anakwah et al, 2015;Blantari et al, 2005;Johnson & Adebayo, 2011). Our findings on the use of the media, especially threat-based messages, align with other reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The study found fear-based messages had no impact on risky driving behaviour and recommended that such tactics be used with caution in road safety campaigns (Anakwah et al, 2015). They further argue that road traffic injury prevention resources could be channelled into other more effective prevention measures than fear-based messages (Anakwah et al, 2015).…”
Section: Educationmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering the nature of risky driving in Ghana (Anakwah et al, 2015), the role of passengers in maintaining sanity is very vital. Passengers are seen as visible checks and regulators on the conduct of both drivers and conductors within the 'Tro-Tro' system.…”
Section: Discussionmentioning
confidence: 99%
“…It will help explain the changing aspects of human behaviour on the roads of Africa and enhance development (Anakwah et al, 2015;Conkle, & West, 2008). On the whole, this will positively enhance planning, policy making, and growth.…”
Section: Discussionmentioning
confidence: 99%